Errors in the Use of Appropriate Verbs in Learning Sinhala with Reference to Tamil Native as a Second Language Students - Shiromi, M. (University of Ruhuna, 2021)
The objective of this research is to identify the patterns of errors in the use of appropriate verbs in Sinhala spoken by Tamil native students. Within the field of second language research, a large number of studies have focused on error analysis. One of the most difficult challenges faced by second language learners of Sinhala is mastering the use of appropriate verbs. Error analysis is crucial for evaluating language application. Thus, data for this study were collected from specific speaking activities which were partaken by a random sample of 50 Sinhala language learners. The Sinhala conversation of Tamil native students was directly observed using recording materials. Both qualitative and quantitative methods were used to analyze primary data. All the identified errors were classified into two sub-types based on the surface structure taxonomy of errors, namely, substitution, and addition. Further, the findings related to the types of errors were compared with the source of those errors. The result of the study revealed wrong substitution to be the main category where students tend to make most of the errors. Thus, this research hopes to support in preparing appropriate teaching and learning materials for Tamil native students who wish to learn Sinhala as a second language.
Keywords: Selecting appropriate verbs; Error analysis; Learning Sinhala as a second language; Substitution types of errors